Housing Drainage Network Evaluation in Education Teacher Road Merauke. (July 2020) - Utary, C; Akbar, M; Kakerissa, Y
Abstract: Increasing population, residential and land development of the narrow lead to flooding or waterlogging during the rainy season. Based on the author's observation that this occurs as a result of population growth and settlement. Areas that were once as a rain water reservoir and the water reservoir tidal inland transformed into residential areas and development centers of economic activity, and social services. The residential area of Merauke teacher education road is low-lying areas and densely populated, thus increasing the flow of water entering the waste stream. Based on the calculation of discharge, obtained Qk = 79, 586, 978.48 m3 / sec. The magnitude of the flood Q Qb = 24, 488, 511, 58 m3 / sec obtained high discharge may cause flooding in the residential area of teacher education path Merauke. So it is necessary to increase the dimensions of the existing channels in order to cope with flooding during the rainy season.